Writing for digital media - Carroll, Brian, 1965- (Routledge, 2010)
"Writing for Digital Media teaches students how to write effectively for online audiences -- whether they are crafting a story for the website of a daily newspaper or a personal blog. The lessons and exercises in each chapter help students build a solid understanding of the ways that the Internet has introduced new opportunities for dynamic storytelling as digital media have blurred roles of media producer, consumer, publisher and reader. Using the tools and strategies discussed in this book, students are able to use their insights into new media audiences to produce better content for digital formats and environments. Fundamentally, this book is about good writing -- clear, precise, accurate, filled with energy and voice, and aimed directly at an audience. Writing for Digital Media also addresses all of the graphical, multimedia, hypertextual and interactive elements that come into play when writing for digital platforms. Learning how to achieve balance and a careful, deliberate blend of these elements is the other primary goal of this text. Writing for Digital Media teaches students not only how to create content as writers, but also how to think critically as a site manager or content developer might about issues such as graphic design, site architecture, and editorial consistency. By teaching these new skill sets alongside writing fundamentals, this book transforms students from writers who are simply able to post their stories online into engaging multimedia, digital storytellers." -- Book cover.